SARS-CoV-2 in children: spectrum of disease, transmission and immunopathological underpinnings (2020)
As the SARS-CoV-2 pandemic unfolds across the globe, consistent themes are emerging with regard to aspects of SARS-CoV-2 infection and its associated disease entities in children. Overall, children appear to be less frequently infected by, and affected by, SARS-CoV-2 virus and the clinical disease COVID-19. Large epidemiological studies have revealed children represent less than 2% of the total confirmed COVID-19 cases, of whom the majority experience minimal or mild disease that do not require hospitalisation. Children do not appear to be major drivers of SARS-CoV-2 transmission, with minimal secondary virus transmission demonstrated within families, schools and community settings. There are several postulated theories regarding the relatively low SARS-CoV-2 morbidity and mortality seen in children, which largely relate to differences in immune responses compared to adults, as well as differences in angiotensin converting enzyme 2 distribution that potentially limits viral entry and subsequent inflammation, hypoxia and tissue injury. The recent emergence of a multisystem inflammatory syndrome bearing temporal and serological plausibility for an immune-mediated SARS-CoV-2-related disease entity is currently under investigation. This article summarises the current available data regarding SARS-CoV-2 and the paediatric population, including the spectrum of disease in children, the role of children in virus transmission, and host-virus factors that underpin the unique aspects of SARS-CoV-2 pathogenicity in children.